CE, concurrent engineering : - Carter, Donald E. (Addison-Wesley Publishing, 1992)
The book that will help you understand the essential dimensions of concurrent engineering and how you will reap the benefits of producing better designed products. You will reduce time-to-market delivery, experience cost savings, and satisfy even more customers